Contrast‐Induced Acute Kidney Injury in Patients Undergoing TAVI Compared With Coronary Interventions. Issue 16 (18th August 2020) - Venturi, Gabriele; Pighi, Michele; Pesarini, Gabriele; Ferrero, Valeria; Lunardi, Mattia; Castaldi, Gianluca; Setti, Martina; Benini, Annachiara; Scarsini, Roberto; Ribichini, Flavio L.
Abstract : Background: Differences in the impact of contrast medium on the development of contrast‐induced acute kidney injury (CI‐AKI) in patients undergoing transcatheter aortic valve implantation (TAVI) or a coronary angiography/percutaneous coronary intervention (CA/PCI) have not been previously investigated. Methods and Results: Patients treated with TAVI or elective CA/PCI were retrospectively analyzed in terms of baseline and procedural characteristics, including preprocedural and postprocedural kidney function. CI‐AKI was defined as a relative increase in serum creatinine concentration of at least 0.3 mg/dL within 72 hours of contrast‐medium administration compared with baseline. The incidence of CI‐AKI in the TAVI versus CA/PCI group was compared. After the exclusion of patients in dialysis and emergency procedures, 977 patients were analyzed; there were 489 patients who had undergone TAVI (50.1%) and 488 patients who had undergone CA/PCI (49.9%). Patients treated by TAVI were older, presenting a higher rate of anemia and chronic kidney disease ( P <0.001 for all comparisons). Consistently, they also had a significantly lower glomerular filtration rate and higher serum creatinine concentration ( P <0.001 for all). However, the occurrence of CI‐AKI was significantly lower in these patients compared with patients treated by a CA/PCI (6.7% versus 14.5%, P <0.001). At multivariate analysis, the TAVI procedure had an independent protective effect on CI‐AKI incidence among total population (odds ratio, 0.334; 95% CI, 0.193–0.579; P <0.001). This observation was confirmed after propensity score matching among 360 patients (180 by TAVI and 180 by CA/PCI; P =0.002). Conclusions: CI‐AKI occurred less frequently in patients undergoing TAVI than in patients undergoing a CA/PCI, despite a worse‐risk profile. The impact of contrast administration on kidney function in patients who had undergone TAVI may be better tolerated because of the hemodynamic changes following aortic valve replacement.